“I am wary of giving too much power to students:” Addressing the “but” in the Principle of Staff-Student Partnership - Murphy, Rebecca; Nixon, Sarah; Brooman, Simon; Fearon, Damian (International Journal for Students as Partners, 2017)
Staff and students coming together to enhance learning is a key educational challenge facing the higher education sector. Literature proposes different ways of achieving this through co-creation, partnership, and collaboration. This paper focuses solely on staff perspectives of a staff-student partnership project aimed at improving feedback strategies. Through a mixed-methods approach, staff in four disciplines in one UK university were questioned in regard to collaborating with students, asked to take part in a co-creation experience, and then invited to take part in a follow-up interview. Findings indicated that staff initially supported greater student engagement in curriculum development but were wary of substantial change in the design of curriculum content. Some doubted the experience and abilities of students in this context. The overarching response was a positive statement followed first with a “but” and then with the issues that could be caused by a partnership approach.